2016
DOI: 10.1159/000448921
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Amyotrophic Lateral Sclerosis: A Population-Based Study in Israel

Abstract: Background: Globally, the annual incidence and prevalence of amyotrophic lateral sclerosis (ALS) are estimated at 1.9 and 4.5 per 100,000 population, respectively. This study is aimed at describing the epidemiology of ALS in Israel in a real-world setting. Methods: A retrospective study was performed using the databases of Maccabi Healthcare Services (MHS), a 2-million-member health maintenance organization in Israel. The study included all MHS adults diagnosed with ALS between 1997 and 2013. In 2013, characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
2
8
2
Order By: Relevance
“…The male to female ratio was 1.63: 1, highly consistent with that of many previous studies [19, 20]. It is argued that possible protective hormonal factors in women may be related to this observed rate [18].…”
Section: Discussionsupporting
confidence: 90%
“…The male to female ratio was 1.63: 1, highly consistent with that of many previous studies [19, 20]. It is argued that possible protective hormonal factors in women may be related to this observed rate [18].…”
Section: Discussionsupporting
confidence: 90%
“…This discrepancy may reflect differences in the proportion of individuals with indigenous ethnic background between both regions of our country. Secondly, we also found a higher incidence of ALS in women, and an increased percentage of bulbar ALS cases, which differs from most of previous reports [4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Meanwhile, the proportion of familial ALS in our population was about 5%, as described in the global literature (4).…”
Section: Effect Of Clinical Features On Survival Of Als Patientscontrasting
confidence: 94%
“…Notably, we found certain particularities in the phenotype of our population compared to what it is described in the literature. Firstly, the mean age at disease onset in the current study was lower than reported in Caucasian series from Europe (4,14-18), Japan (19), and Israel (20), but it coincides with values observed in the United States (21), Brazil (22), and Uruguay (11). Nonetheless, a previous investigation performed in the northern region of Mexico showed that the mean age at disease onset was around 47 years (13), much lower than observed in the current study.…”
Section: Discussionsupporting
confidence: 81%